2010
DOI: 10.1002/ejoc.201001393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Dibenzothiophenes – An Efficient Three‐Step Approach Based on Pd‐Catalyzed C–C and C–S Bond Formations

Abstract: A novel and efficient three-step protocol for synthesizing functionalized dibenzothiophenes (DBTs) from common starting materials and by using palladium-catalyzed carboncarbon and carbon-sulfur bond formations is presented. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Zuschriften thioethers.E lectron-rich and -deficient aryl halides were equally effective.M oreover,v arious substituents were tolerated in the ortho, meta,and para positions to the site of C À S coupling,a nd the corresponding products were isolated in excellent yields.N otably,e ven unprotected amines (primary amine and unprotected indole) did not impede the efficiency of the transformation. Them ethod proved to be compatible with ether (11, 17, 22,and 24), ketone (29), aldehyde (7), ester (9 and 10), and cyano (6 and 27)functional groups.Moreover, pharmaceutically and agrochemically important heterocycles, such as furan, thiophene,indole,and pyrimidine,gave rise to equally high yields of the corresponding sulfide coupling products as standard aromatic or polyaromatic substrates (7,8,21,22,a nd 26;T able 1). Fore xample, 33 is the final intermediate towards key bioactive compounds,s hown to have strong affinity for nicotinic acetylcholine receptors with potential relevance in the treatment of Alzheimersdisease.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Zuschriften thioethers.E lectron-rich and -deficient aryl halides were equally effective.M oreover,v arious substituents were tolerated in the ortho, meta,and para positions to the site of C À S coupling,a nd the corresponding products were isolated in excellent yields.N otably,e ven unprotected amines (primary amine and unprotected indole) did not impede the efficiency of the transformation. Them ethod proved to be compatible with ether (11, 17, 22,and 24), ketone (29), aldehyde (7), ester (9 and 10), and cyano (6 and 27)functional groups.Moreover, pharmaceutically and agrochemically important heterocycles, such as furan, thiophene,indole,and pyrimidine,gave rise to equally high yields of the corresponding sulfide coupling products as standard aromatic or polyaromatic substrates (7,8,21,22,a nd 26;T able 1). Fore xample, 33 is the final intermediate towards key bioactive compounds,s hown to have strong affinity for nicotinic acetylcholine receptors with potential relevance in the treatment of Alzheimersdisease.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[20] Ar emaining challenge in carbon-heteroatom bond formation, and in metal-catalyzed transformations more generally,i st oa chieve site selectivity in couplings of poly-(pseudo)halogenated arenes.W hile isolated examples exist, [12] there is al ack of generality in substrate.S ubtle variations in steric or electronic features frequently lead to diminished or abolished selectivities. [5b] In line with this,o ur test of one of the most employed Pd 0 -derived thiolation catalysts,P d 2 dba 3 /DPEPhos, [21] showed functionalization at the CÀOTfs ite (88 %) in am ixture with difunctionalized product (8 %) and remaining starting material (4 %) when 5-bromo-4-methylpyridin-2-yl trifluoromethanesulfonate was used (see Scheme 3,entry 1,bottom). When the air-sensitive and more labile Pd I bromo dimer was employed under our conditions,p oor conversion into the desired product was observed (20 %), with as ignificant amount of starting material remaining.T his suggests that the Pd I bromo dimer might behave as ap recatalyst, releasing Pd 0 species in situ, which might subsequently be trapped as Pd II ate complexes by the sulfur nucleophile (see Scheme 3, entry 2, bottom) or alternatively be deactivated.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…For the synthesis of sulfur-containing heterocycles usually metal sulfides, thioesters, or thioethers are employed as starting materials, and first-or second-row transition-metal complexes serve as catalysts. To achieve C-C 9-12 or C-S [13][14][15][16][17][18][19][20] coupling involved in the ring closure process, activation of C-H, [9][10][11][12][13][14][15][16][17][18][19][20] C-X (X = Br or I) 15,18,20 or C-S 14,17 bonds is a prerequisite.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Several straightforward methods for the synthesis have been reported. [6] These methods include multistep procedures, require halogenated or metalated compounds, and are neither atom-nor time-economical nor environmentally friendly. Application of transition-metal catalysts is limited because of the known poisoning effect of sulfur.…”
mentioning
confidence: 99%
“…Therefore, we screened different additives in subsequent experiments. We found that the reaction can be promoted by using iodoarenes as additives ( Table 1, entries [3][4][5][6]. Application of p-fluoroiodobenzene led to the target product in 77 % yield.…”
mentioning
confidence: 99%